Review articleLow-dose-rate or high-dose-rate brachytherapy in treatment of prostate cancer – between options - Skowronek, Janusz (Journal of Contemporary Brachytherapy, 2013)
Purpose: Permanent low-dose-rate (LDR-BT) and temporary high-dose-rate (HDR-BT) brachytherapy are competitive techniques for clinically localized prostate radiotherapy. Although a randomized trial will likely never to be conducted comparing these two forms of brachytherapy, a comparative analysis proves useful in understanding some of their intrinsic differences, several of which could be exploited to improve outcomes. The aim of this paper is to look for possible similarities and differences between both brachytherapy modalities. Indications and contraindications for monotherapy and for brachytherapy as a boost to external beam radiation therapy (EBRT) are presented. It is suggested that each of these techniques has attributes that advocates for one or the other. First, they represent the extreme ends of the spectrum with respect to dose rate and fractionation, and therefore have inherently different radiobiological properties. Low-dose-rate brachytherapy has the great advantage of being practically a one-time procedure, and enjoys a long-term follow-up database supporting its excellent outcomes and low morbidity. Low-dose-rate brachytherapy has been a gold standard for prostate brachytherapy in low risk patients since many years. On the other hand, HDR is a fairly invasive procedure requiring several sessions associated with a brief hospital stay. Although lacking in significant long-term data, it possesses the technical advantage of control over its postimplant dosimetry (by modulating the source dwell time and position), which is absent in LDR brachytherapy. This important difference in dosimetric control allows HDR doses to be escalated safely, a flexibility that does not exist for LDR brachytherapy. Conclusions : Radiobiological models support the current clinical evidence for equivalent outcomes in localized prostate cancer with either LDR or HDR brachytherapy, using current dose regimens. At present, all available clinical data regarding these two techniques suggests that they are equally effective, stage for stage, in providing high tumor control rates.